Feeding policies for dairy cows in the "zona da mata" of Minas Gerais. II. Effect of stocking rate on the relationship between herbage supply and demand - Assis, Airdem Gonçalves de (Pesquisa Agropecuaria Brasileira, 2014)
A computer simulation model was used to investigate the effects of stocking rate (0.2, 0.4, 0.6 and 1.2 cows/ha-1) change on the relationship between herbage availability and nutrient demand for dairy cows yielding (1,000, 2,500 and 4,000 kg.lactation-1) at two calving (April and October) seasons. The results are discussad in relation to some qualitative and quantitative limitations of grazed swards for dairy cows over the year. It was concluded that: 1. low herbage availability during the dry season (April-September) is probably the main factor limiting animal performance; 2. energy seems to be a more limiting nutrient in the pasture than protein; 3. October should be more suitable for calving than April and 4. 0.6 and 0.4 cows.ha-1 appear to be the more adequate stocking rates for those dairy systems with and without supplementary feeding, respectively.